A Case of Primary Sjögren’s Syndrome Presenting as Mass-Like Encephalitis, With Progression to Neuromyelitis Optica Spectrum Disorder - Hyun-Jung LEE; Sung Hae CHANG; Eun Ha KANG; Yun Jong LEE; Yeong Wook SONG; You-Jung HA (Archives of Rheumatology, 2017)
Neuromyelitis optica is an idiopathic inflammatory demyelinating disease of the central nervous system (CNS) that predominantly affects the optic nerves and spinal cord. With the discovery of the pathogenic anti-aquaporin-4 (AQP4) antibody, the disease was recognized as part of a spectrum of autoimmune diseases that target AQP4, collectively referred to as neuromyelitis optica spectrum disorder (NMOSD). NMOSD consists of conditions that affect various parts of the CNS with the AQP4 antibody. In this article, we report a 43-year-old female patient who was initially diagnosed with primary Sjögren’s syndrome (pSS) with CNS involvement, but was later diagnosed with overlapping pSS and NMOSD, which required more intensive treatment. The patient presented with fever, headache, dysarthria, and left-side weakness, and brain imaging showed a mass-like edematous lesion in the right frontoparietal region. She also complained of xerostomia and was diagnosed with pSS by salivary scintigraphy, anti-Sjögren’s syndrome A positivity, and minor salivary gland biopsy. Under the diagnosis of pSS with CNS involvement in the form of tumefactive encephalitis, she was treated with high-dose steroids and monthly intravenous cyclophosphamide therapy. However, three months later, she developed a sudden decrease in right visual acuity and had right optic neuritis. Her serum was positive for the anti-AQP4 antibody, and she was finally diagnosed with overlapping NMOSD and pSS. She was treated with steroid pulse therapy and plasmapheresis. Therefore, in patients with pSS presenting with cerebral white matter lesions, even when optic neuritis or myelitis is absent, evaluations for the anti-AQP4 antibody should be considered to detect and treat NMOSD accordingly.